Transformasi Pedagogis Guru: Kreatifitas Guru Pendidikan Agama Kristen di Era Postmodern - Pantan, Frans (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2024)
This study examines teacher pedagogy's transformation through a creative and postmodern approach in Christian Religious Education. In the postmodern era, filled with complexity and dynamics, teachers must have high creativity, flexibility, and interdisciplinary abilities in the learning process. The research method used is qualitative, with data collection techniques used in library research. The research procedure includes three stages: first, examining the basic concepts of teacher creativity; second, identifying indicators of creative teachers; and third, formulating strategies for developing teacher creativity in the postmodern era. The study results show that teacher creativity is greatly influenced by deep knowledge, innovation in teaching methods, and digital technology. A postmodern approach that emphasizes flexibility, interdisciplinarity, and innovation in learning is essential to overcome the challenges of the times and improve the quality of education. Implementing Good Corporate Governance (GCG) principles in school management, improving learning facilities, and regular training and developing teacher skills are critical strategies for creating a conducive learning environment. Thus, this study provides practical and theoretical guidance to enhance the creativity of Christian Religious Education teachers and produce a generation that is intelligent, skilled, and Christ-like in character.